2014
DOI: 10.5194/hess-18-3837-2014
|View full text |Cite
|
Sign up to set email alerts
|

Flow regime change in an endorheic basin in southern Ethiopia

Abstract: Abstract. Endorheic basins, often found in semi-arid and arid climates, are particularly sensitive to variation in fluxes such as precipitation, evaporation and runoff, resulting in variability of river flows as well as of water levels in endpoint lakes that are often present. In this paper we apply the indicators of hydrological alteration (IHA) to characterise change to the natural flow regime of the Omo-Ghibe Basin in southern Ethiopia. Little water resource infrastructure has been developed in the basin to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 62 publications
0
11
1
Order By: Relevance
“…Land cover conversions such as from natural vegetation to cropland and settlement are generally assumed to enhance total and peak flow volumes (Legesse et al 2010). However, this assumption was not supported by empirical data particularly for large-sized watersheds in Ethiopia (Gebrehiwot et al 2014;Worku et al 2014). Thus, we found it difficult to explain the increasing signals that we found for Qann, Qwet, and high-flow indicators (Qmax1day, Qmax7day, and Qmax30day) with land cover conversations.…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations
“…Land cover conversions such as from natural vegetation to cropland and settlement are generally assumed to enhance total and peak flow volumes (Legesse et al 2010). However, this assumption was not supported by empirical data particularly for large-sized watersheds in Ethiopia (Gebrehiwot et al 2014;Worku et al 2014). Thus, we found it difficult to explain the increasing signals that we found for Qann, Qwet, and high-flow indicators (Qmax1day, Qmax7day, and Qmax30day) with land cover conversations.…”
Section: Discussioncontrasting
confidence: 55%
“…Findings in our study are generally different from previous research works (Bewket and Sterk 2005;Melesse et al 2009;Tesemma et al 2010;Rientjes et al 2011;Gebrehiwot et al 2014) that reported no significant changes for annual, wet season and high-flow magnitudes and downward trends for low-flow magnitudes, particularly in the upper Abbay River Basin. However, there are some recent studies (Worku et al 2014;Degefu and Bewket 2017) that found evidences of upward changes in dry weather flow and extreme lowflow magnitudes. Another study (Berahanu et al 2014) had also reported decreasing changes in the mean zero flow days and coefficient of variation in streamflow magnitudes for Ethiopian rivers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most widely used hydrologic metrics are called indicators of hydrologic alteration (IHA), which include 33 hydrologic parameters describing a wide array of flow characteristics, including the magnitude of monthly runoff, the magnitude of annual extreme streamflow, the timing of annual extreme flow, the frequency and duration of high and low flow pulse and the rate and frequency of streamflow changes [13]. IHA metrics have been successfully applied to evaluate hydrological alterations in a suite of watersheds located in arid, semi-arid, and humid regions [14][15][16]. However, previous studies have also concluded that there is statistical redundancy in the parameters of IHA and that some parameters are inter-correlated [17,18].…”
Section: Introductionmentioning
confidence: 99%